EVALUATION OF THE RELATIONSHIP BETWEEN SPIRITUAL WELL-BEING AND SURGICAL FEAR IN LIVER TRANSPLANT CANDIDATES - Kübra KAYAOĞLU (Rojan GÜMÜŞ, 2023)
This study was conducted to evaluate the relationship between spiritual well-being and surgical fear in liver transplant candidates. This study is a cross-sectional study conducted with 124 liver transplant candidate patients admitted to a university liver transplant center. Personal Information Form, Spiritual Well-Being Scale (SWBS), and Surgical Fear Scale (SFS) were used to collect data. It was determined that the patients' spiritual well-being was 24,59 ± 9,20 and their surgical fear was 40,11 ± 10,94. In the study, it was determined that there was a statistically negative correlation between the patients' spiritual well-being and surgical fear (r=-0.248, p˂0.01). This study proved that liver transplant candidates with high levels of spiritual well-being have lower levels of surgical fear. For this reason, awareness of spiritual well-being should be developed in healthcare professionals and it is recommended that they provide healthcare services that provide moral and social support to patients. Keywords: Liver transplant, surgical fear, spiritual well-being.